Li 1s core exciton in LiH studied by x-ray Raman scattering spectroscopy. (19th December 2018) - Paredes-Mellone, O A; Stutz, G E; Ceppi, S A; Arneodo Larochette, P; Huotari, S; Gilmore, K
Abstract: The Li 1 s core excitation spectra in LiH was studied by means of x-ray Raman scattering (XRS) spectroscopy in a wide range of momentum transfers q . The analysis of the near-edge region of the measured spectra in combination with q -dependent ab initio calculations of XRS spectra based on the Bethe–Salpeter equation (BSE) reveals that the prominent peak at the excitation onset arises from two main contributions, namely a pre-edge peak associated to a p -type core exciton and strong transitions to empty states near the bottom of the conduction band, which is in contrast to previous experimental studies that attributed that feature to a single excitonic peak. The p -like angular symmetry of the core exciton is supported by BSE calculations of the relative contributions to the XRS spectra from monopole and dipole transitions and by the observed decrease of its normalised intensity for increasing momentum transfers. Higher energy spectral features in the measured XRS spectra are well reproduced by BSE, as well as by real-space multiple-scattering calculations.